Persian Gulf 2021–22 - Hameed, Sameena. author. aut Link
XXVI, 553 p. 3 illus., 1 illus. in color.
Keywords: The Persian Gulf 2021-22 is the ninth in the annual Persian Gulf Series published by MEI@ND. It is a detailed analysis of India’s bilateral relations with the nine countries in the Persian Gulf region and the Gulf Cooperation Council (GCC), and focuses on the developments of 2020 and 2021. It offers a comprehensive account of the internal politics, economic situations, foreign policy, security challenges and social developments in the Persian Gulf countries and India’s strategic, political, economic and cultural engagements with the region. The book also offers policy recommendations for India based on the current state of affairs. Sameen Hameed is Assistant Professor in Middle Eastern Studies in Jawaharlal Nehru University, New Delhi. Her areas of specialization include the Middle Eastern economy, India's economic relations with the Middle East and energy security issues. She has authored several research and policy papers, and is the editorof Youth Bloom in GCC (2022). Md. Muddassir Quamar is Associate Fellow at Manohar Parrikar Institute for Defence Studies and Analyses and holds a Ph.D. in Middle East studies from Jawaharlal Nehru University. He is a prolific writer on contemporary developments in the Middle East and India-Middle East relations. P. R. Kumaraswamy is Professor of contemporary Middle East in Jawaharlal Nehru University (JNU), New Delhi. Since joining JNU in September 1999, he has been researching, teaching, and writing on various aspects of the contemporary Middle East. His works include Squaring the Circle: Mahatma Gandhi and the Jewish National Home (2018) and India’s Israel Policy (2010).